Alternative splicing factor ASF/SF2 is down regulated in inflamed muscle. Issue 8 (30th March 2006) - Xiong, Z; Shaibani, A; Li, Y-P; Yan, Y; Zhang, S; Yang, Y; Yang, F; Wang, H; Yang, X-F
Abstract : Background: In our recent studies, alternative splicing has been shown to have a major role in inflammation and autoimmune muscle diseases. Aim: To examine the novel hypothesis that the expression of an essential alternative splicing factor, alternative splicing factor 2 (ASF/SF2), is modulated in muscle inflammation. Methods: ASF/SF2 expression in muscle biopsy samples from eight patients with inflammatory myopathy and six non-myositic controls was determined by using western blot with anti-ASF/SF2 antibodies. To further elucidate the mechanism of reduced ASF/SF2 expression in inflamed muscle, differentiated C2C12 myotubes were stimulated with proinflammatory cytokine tumour necrosis factor α (TNFα), followed by western blot analysis of ASF/SF2 expression. Results: ASF/SF2 expression in the muscle biopsy samples from patients with inflammatory myopathy was found to be lower (mean of relative densitometric units 41.1 (2SD 20.7)) than that of the non-myositic controls (mean of relative densitometric units 76.7 (39.6); p<0.05). In addition to this, ASF/SF2 expression was seen to be significantly down regulated (sevenfold) in C2C12 myotubes compared with expression variations in the β-actin control (0.62-fold; mean 1.22 (0.40); p<0.05). Conclusion: Collectively, it is shown, for the first time, that alternative splicing factor ASF/SF2 is down regulated in autoimmune inflammatory myositis—potentially via a TNFα-mediated pathway. The development of (1) novel autoantigen isoform microarrays for disease diagnosis and prognosis; (2) novel autoantigen-tolerising treatments for autoimmune diseases; and (3) novel splicing-redirection treatments can be facilitated by the ongoing study of alternative splicing of autoantigen transcripts.